2005
DOI: 10.1002/dvdy.20423
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the natriuretic peptide precursor gene cluster in vertebrates reveals loss of ANF and retention of CNP‐3 in chicken

Abstract: We identified and characterized the chicken natriuretic peptide precursor gene cluster and found its organization to be highly conserved compared with the mammalian Nppb-Nppa cluster. However, phylogenetic analysis indicated that the putative chicken natriuretic peptide precursor genes are the homologues of CNP-3 and Nppb, respectively. Comparative expression analysis revealed that, in human, mouse, and rat hearts, Nppb is a novel marker for the differentiating working myocardium. Its expression pattern is str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 66 publications
(49 reference statements)
1
13
0
1
Order By: Relevance
“…The ligand of this receptor, CNP, on the other hand, has been suggested to act through an autocrine/paracrine mechanism, since the blood levels of this protein are very low . In situ hybridization analysis of spatial CNP-3 expression within the developing chick limb bud at HH stage 36 revealed its main expression within the mesenchyme deep to the dermis outside the chondrogenic mesenchymal chore region [Houweling et al, 2005]. RT-PCR results at mRNA level shown in this study support this information from the literature.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The ligand of this receptor, CNP, on the other hand, has been suggested to act through an autocrine/paracrine mechanism, since the blood levels of this protein are very low . In situ hybridization analysis of spatial CNP-3 expression within the developing chick limb bud at HH stage 36 revealed its main expression within the mesenchyme deep to the dermis outside the chondrogenic mesenchymal chore region [Houweling et al, 2005]. RT-PCR results at mRNA level shown in this study support this information from the literature.…”
Section: Discussionsupporting
confidence: 83%
“…A recent study has identified and characterized the chicken natriuretic peptide precursor gene cluster and found its organization to be highly conserved compared with the mammalian Nppb-Nppa cluster [Houweling et al, 2005]. However, phylogenetic analysis indicated that the putative chicken natriuretic peptide precursor genes are the homologues of CNP-3 and Nppb, respectively [Houweling et al, 2005]. In addition, the amino acid sequence of chicken CNP-3 shows high homology to that of human CNP [Houweling et al, 2005].…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Both genes are also expressed in the adult heart (Cameron et al, 1996;Houweling et al, 2005) but Nppa is downregulated in the ventricles around birth to become restricted to the atria and the ventricular conduction system (Moorman and Christoffels, 2003). Both genes are strongly induced in the ventricles by stress and heart failure, and have become reliable clinical and experimental biomarkers for the severity of hypertrophy and heart failure (Guo et al, 2011;Sergeeva et al, 2014;Troughton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%